The Relationship Between the Implementation of Basic Management Functions and Service Quality in the Outpatient Department of the ObstetricsClinic at Primaya Hospital North Bekasi in 2025 - Lispeno Waty Agustina Br Sipayung; Felix Kasim; Sri Melda Br Bangun (JURNAL KESMAS DAN GIZI (JKG), 2026)
In the era of globalization characterized by increasing competition, the demand for improved hospital service quality continues to rise. Patients as healthcare service users have become more selective and critical in evaluating the quality of services provided. Therefore, hospitals are required to continuously enhance service quality through innovation and effective management. Service quality is not only determined by the availability of facilities and technology, but is also significantly influenced by the implementation of management functions, including planning, organizing, actuating, and controlling (POAC). The optimal application of these management functions can promote a more efficient, integrated, and patient-oriented service system.  This study employed a quantitative approach with a cross-sectional design to analyze the relationship between POAC management functions and service quality at the Obstetrics Outpatient Clinic of Primaya Hospital Bekasi Utara. The study population consisted of 8,321 patients, with a sample of 90 respondents determined using the Slovin formula. Data analysis included univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using logistic regression.  The results showed that most respondents rated the implementation of management functions as good, including planning (66.7%), organizing (70.0%), actuating (65.6%), and controlling (74.4%). Service quality was also perceived as good by the majority of respondents (72.2%). Bivariate analysis indicated that all management function variables were significantly associated with service quality (p ≤ 0.001). Multivariate analysis revealed that planning, actuating, and controlling had significant effects on service quality, while organizing did not show a statistically significant effect. Among all variables, planning was identified as the most dominant factor.  In conclusion, the implementation of POAC management functions plays a crucial role in improving service quality, with planning as the most influential factor that needs to be continuously optimized.